CLIMATE CHANGE AND MADHYA PRADESH: जलवायु परिवर्तन और मध्यप्रदेश - Jain, Abhay (International Journal of Research -GRANTHAALAYAH, 2015)
The issue of balance between development and environment has been going on for a long time, but due to the development cycle, the environment is being ignored somewhere and such situations are facing us in the form of challenge and compulsion today. Despite the implementation of many resolutions, promises, policies and programs etc., environmental challenges remain before us. There is a lot of fluctuation in the weather, excessive rain or drought is not a coincidence but an indicator and result of dangerous changes in the environmental conditions. Dealing with climate change is of paramount importance not only for our health but also to benefit the health of generations to come. Climate change has the greatest impact on the poor and the lower strata of society as they have limited resources. Climate change has had a negative impact on agriculture. Due to which the problem of food grains is arising due to reduction in yield. It is necessary to consider the expansion, research and development of agricultural facilities, as rising global temperatures have increased the magnitude of seasonal events, loss of crops, water scarcity and other crises. There is a need to take revolutionary decisions to stop the flow of destruction caused by climate change. Laws are available for environmental protection, but there is a need for proper observance and more active public consciousness so that development and environment remain balanced. विकास और पर्यावरण के बीच संतुलन की बात लम्बे समय से चली आ रही है, लेकिन विकास चक्र के चलते कहीं न कहीं पर्यावरण की अनदेखी होती आ रही है और ऐसी स्थितियाँ आज हमारे सामने चुनौती एवं सकंट के रूप में है। अनेक संकल्प, वादे, नीतियाँ और कार्यक्रम आदि के क्रियान्वयन के बावजूद भी पर्यावरण चुनौतियाँ हमारे सामने है। मौसम में बहुत अधिक उतार-चढ़ाव हो रहे है, अधिक बरसात या सूखा पड़ना संयोग नहीं बल्कि पर्यावरण परिस्थितियों में आ रहे खतरनाक बदलाव के सूचक और परिणाम है। जलवायु परिवर्तन से निपटना न केवल हमारे स्वास्थ्य के लिये बल्कि आने वाली पीढ़ियों के स्वास्थ्य को लाभ पहुँचाने के लिये सर्वाधिक महत्वपूर्ण है। जलवायु परिवर्तन का सबसे ज्यादा प्रभाव गरीबों और समाज के निचले तबको पर पड़ता है क्योंकि उनके पास साधन सीमित होते है। जलवायु परिवर्तन की वजह से कृषि पर काफी नकारात्मक असर पड़ा है। जिससे पैदावार में कमी के कारण खाद्यान्न की समस्या उत्पन्न हो रही है। कृषि सुविधाओं के विस्तार, अनुसंधान व विकास पर विचार करना जरूरी है, क्योंकि बढ़ते वैश्विक तापमान ने मौसमी घटनाओं की भयावहता, फसलों का नुकसान, पानी की कमी एवं अन्य संकटों मंे वृद्धि की है। जलवायु परिवर्तन के कारण होने वाली विनाशलीला के प्रवाह को रोकने के लिये क्रांतिकारी निर्णय लेने की आवश्यकता है। पर्यावरण संरक्षण के लिए कानून तो उपलब्ध है किन्तु उनका समुचित पालन और जन चेतना को अधिक सक्रिय करने की आवश्यकता है ताकि विकास और पर्यावरण मंे संतुलन बना रहे।